2022
DOI: 10.29240/jba.v6i1.4069
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling Method to Improve Vocabulary for Non-Native Arabic Speaker Children

Abstract: The purpose of this study is to investigate; (1) the method of using storytelling to learn Arabic vocabulary, (2) the emotional state of students when using storytelling to learn, and (3) the impact of storytelling on boosting students' Arabic vocabulary. This study uses Mixed Method Research. Students from the al-Imam Islamic boarding school Metro Kibang East Lampung, a total of 40 students, participated in the study. Observation and testing are the methods used to obtain data. The method of observation was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
1
0
0
1
Order By: Relevance
“…A few studies have found that mobile application instruction has an effect on student motivation. The findings are consistent with Akla (2022), highlighting the teacher interviews and stating that the student's technical and presentation skills had improved, as well as their engagement and learning motivation.…”
Section: Discussionsupporting
confidence: 82%
“…A few studies have found that mobile application instruction has an effect on student motivation. The findings are consistent with Akla (2022), highlighting the teacher interviews and stating that the student's technical and presentation skills had improved, as well as their engagement and learning motivation.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, a study by Akla (2022) emphasised the narrative strategy as a means of assisting youngsters who are not native Arabic speakers in increasing their vocabulary. According to the study's findings, kids strove to mimic every word their teacher spoke until they got it right.…”
Section: Literature Review Vocabulary Studiesmentioning
confidence: 99%
“…Namun kesalahan dalam pembelajaran bahasa bukanlah hal yang aneh, karena kesalahan adalah sebahagian dari proses belajar yang tidak dapat dielakkan. Hal ini disokong oleh Akla (2022) yang berpendapat bahawa masalah yang dihadapi oleh pelajar dalam pengajaran bertutur adalah pada perbendaharaan kata, nahu, morfologi dan susunan ayat. Justeru itu, fokus kajian banyak dilakukan pada aspek yang didapati menjadi cabaran ialah pemerolehan kata (kosa kata) (Isnaini & Huda, 2020) dan nahu (Jamaluddin & Baharudin, 2021;Rahman, et al, 2020).…”
Section: Dimensi Leksis and Nahuanunclassified